Review of medical discharge summaries and medical documentation in a metropolitan hospital: impact on diagnostic‐related groups and Weighted Inlier Equivalent Separation. Issue 7 (11th July 2013) - Chin, N.; Perera, P.; Roberts, A.; Nagappan, R.
Abstract Background Accurate and comprehensive clinical documentation is crucial for effective ongoing patient care, follow up and to optimise casemix‐based funding. Each Diagnostic Related Group (DRG) is assigned a 'weight', leading to Weighted Inlier Equivalent Separation (WIES), a system many public and private hospitals in Australia subscribe to. Aims To identify the top DRG in a general medical inpatient service, the completeness of medical discharge documentation, commonly missed comorbidities and system‐related issues and subsequent impact on DRG and WIES allocation. Methods One hundred and fifty completed discharge summaries were randomly selected from the top 10 medical DRG in our health service. From a detailed review of the clinical documentation, principal diagnoses, associated comorbidities and complications, where appropriate, the DRG and WIES were modified. Results Seventy‐two (48%) of the 150 reviewed admissions resulted in a revision of DRG and WIES equivalent to an increase of AUD 142 000. Respiratory‐based DRG generated the largest revision of DRG and WIES, while 'Cellulitis' DRG had the largest relative change. Twenty‐seven per cent of summaries reviewed necessitated a change in coding with no subsequent change in DRG allocation or WIES. Acute renal failure, anaemia and electrolyte disturbances were the most commonly underrepresented entities in clinical discharge documentation. Seven patients had their WIES downgraded. Conclusion Comprehensive documentation of principal diagnosis/diagnoses, comorbidities and their complications is imperative to optimal DRG and WIES allocation. Regular meetings between clinical and coding staff improve the quality and timeliness of medical documentation, ensure adequate communication with general practitioners and lead to appropriate funding.